Impact of Climate Change on Wintering Ground of Japanese Anchovy (Engraulis japonicus) Using Marine Geospatial Statistics - Liu, Shuhao; Liu, Yang; Alabia, Irene D.; Tian, Yongjun; Ye, Zhenjiang; Yu, Haiqing; Li, Jianchao; Cheng, Jiahua (Frontiers in Marine Science, 2020)
Distribution and fluctuations in abundance of small pelagic species such as anchovy are largely affected by climate change. We hypothesized that the future projected rise in temperature will result to a northward shift of Japanese anchovy (Engraulis japonicus) habitat and a subsequent increase in relative abundance. To test this hypothesis, we explored the link between the Japanese anchovy abundance and environmental conditions using machine–learning and statistical models. The models were fitted with catch per unit effort (CPUE) as the response variable and remotely sensed data of sea surface temperature (SST), sea surface chlorophyll-a, assimilated information of sea surface salinity, meridional and zonal ocean currents, and depth as environmental covariates. Our results showed that the abundance of E. japonicus was significantly influenced by environmental factors. In particular, salinity front and SST highlight strong relationships with winter CPUE distribution. Based on these models, The results reinforced our hypothesis and showed that warming ocean will drive a substantial shift in Japanese anchovy habitat in the China Seas. SST and CPUE showed negative correlations with the El Niño Southern Oscillation index. These findings underpin ramifications of climate-driven habitat shift of small pelagic fish species on the regional marine ecosystem in the China seas.